Culture and Syntax: A Qualitative Comparative Study on How Cultural Norms Shape Sentence Structure - Kamaluddin, Mohamad Ihsan (Journal of English Education Forum (JEEF), 2025)
This study investigates how cultural norms shape syntactic structures by comparing sentence construction in Indonesian and English using a qualitative literature review approach. Through a critical analysis of recent linguistic and cross-cultural studies, the research explores how cultural values such as collectivism, individualism, politeness orientation, and communication context influence syntactic features like word order, voice, ellipsis, and pragmatic forms. The findings demonstrate that Indonesian syntax, with its flexibility in structure, frequent use of passive constructions, and reliance on contextual ellipsis, aligns with high-context and collectivist cultural values that emphasize relational harmony and indirectness. In contrast, English syntax, characterized by more rigid word order and subject-centered constructions, reflects low-context and individualistic norms that value clarity and directness. These syntactic tendencies are not merely linguistic choices but manifestations of deeper cultural orientations. The study emphasizes the importance of integrating cultural awareness into language education and linguistic technology, as syntactic forms carry social meanings that affect communication outcomes. It concludes that syntax should be understood not only as a structural aspect of language but also as a culturally embedded system shaped by the social and cognitive frameworks of its speakers.